Prose poetry an introduction - Hetherington, Paul 1958- (Princeton University Press, 2020)
An engaging and authoritative introduction to an increasingly important and popular literary genreProse Poetry is the first book of its kind—an engaging and authoritative introduction to the history, development, and features of English-language prose poetry, an increasingly important and popular literary form that is still too little understood and appreciated. Poets and scholars Paul Hetherington and Cassandra Atherton introduce prose poetry’s key characteristics, chart its evolution from the nineteenth century to the present, and discuss many historical and contemporary prose poems that both demonstrate their great diversity around the Anglophone world and show why they represent some of today’s most inventive writing.A prose poem looks like prose but reads like poetry: it lacks the line breaks of other poetic forms but employs poetic techniques, such as internal rhyme, repetition, and compression. Prose Poetry explains how this form opens new spaces for writers to create riveting works that reshape the resources of prose while redefining the poetic. Discussing prose poetry’ s precursors, including William Wordsworth and Walt Whitman, and prose poets such as Charles Simic, Russell Edson, Lydia Davis, and Claudia Rankine, the book pays equal attention to male and female prose poets, documenting women’s essential but frequently unacknowledged contributions to the genre.Revealing how prose poetry tests boundaries and challenges conventions to open up new imaginative vistas, this is an essential book for all readers, students, teachers, and writers of prose poetry
Keywords: Geschichte; American poetry; Baudelaire; France; French; Macpherson; Ossian; analysis; box; contemporary prose poetry; digital media; famous prose poems; famous prose poets; flaneur; fragment; guidebook; handbook; how is prose poetry different from poetry; how to interpret prose poetry; how to read prose poetry; neo surreal; neo surrealism; postmodern writing; romantic fragment; surrealism; surrealists; symbolism; symbolists; what is difference between prose poetry and poetry; what is prose poetry; who writes prose poetry; LITERARY CRITICISM / Poetry; Prose poems -- History and criticism; Englisch; Prosagedicht